Adsorption of Zn(II) on graphene oxide prepared from low‐purity of amorphous graphite. (21st September 2016) - Yang, Qiang; Yang, Guangcheng; Peng, Weijun; Song, Shaoxian
Abstract : The adsorption of Zn(II) in aqueous solutions on graphene oxide (GO) prepared from low‐purity of natural amorphous graphite has been studied in this work. The study was performed through the measurements of Zeta potential, atomic force microscope, Fourier transform infrared spectrum and X‐ray photoelectron spectroscopy. The results indicated that the adsorption followed the Langmuir model with the maximum Zn(II) adsorption capacity of 73 mg/g at pH 7.0. In addition, the adsorption was well described by the pseudo‐second‐order kinetics model. The mechanism of the Zn(II) adsorption on GO was mainly attributed to chemical adsorption through complexation reaction between Zn(II) and hydroxyl or carboxyl groups on the GO sheets, while the electrostatic interaction also contribute to the whole interaction. Copyright © 2016 John Wiley & Sons, Ltd.